Oral Hygiene Examination And Dental Health Education Of School Children At Pesantren Kampung Tauhid Sriwijaya South Sumatra - Martha Mozartha; Sri W. Rais; Siti Rusdiana Puspa Dewi; Danica Anastasia; Arya Prasetya Beumaputra; Hema Awalia (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Previous studies have shown that the majority of children in Indonesia have poor oral hygiene. Children who attend boarding school are sometimes facing difficulties in accessing dental health providers. In this kind of situation, knowledge of oral health and how to do a proper dental cleaning is crucial and must be mastered not only by students but also their teachers who spend most time with them at the boarding school. This goal can be achieved by the collaboration of dental public health and the school and community members.